Students’ Writing Process for Project Ibunka: A Case Study of EFL Writers - Elis Homsini Maolida; Gilang Mustika (Journal of English Language Teaching and Linguistics, 2018)
Project Ibunka is an online cross-cultural exchange program that has a text-based bulletin board discussion where the students from various cultures can write about several topics from school life to social issues and give comments to each other. In the context of this study, this program was used  as a media to develop students’ writing skill. This study aims to reveal the students’ writing process in the Project. This case study involved 15 English department students who took part in the project for more than twelve weeks. The data were collected through observation and interview and they were analyzed qualitatively. The findings reveal that most students experienced all stages of writing process from pre writing, drafting, revising, editting and publishing. However, the arrangement, the way the students put the stages into practice and how they applied their strategies in each stage were various. In pre writing, for example, the students experienced different mixture of conversation, silent thinking, reading some sources, clustering, and outlining strategies. In drafting, most students focused on writing their ideas and avoided losing the ideas by mixing the language while the others did revision and editting during drafting process. In revising and editting, the students asked for feedback and utilized technologies to help them improve their writing. Eventhough all students published their writing in Project Ibunka, each student had different experience of publishing process. It shows that all writers have their own way and strategy that work for them and what works for a writer may not work for another and vice versa.